2021
DOI: 10.1038/s41467-021-22565-7
|View full text |Cite
|
Sign up to set email alerts
|

Selenoprotein W ensures physiological bone remodeling by preventing hyperactivity of osteoclasts

Abstract: Selenoproteins containing selenium in the form of selenocysteine are critical for bone remodeling. However, their underlying mechanism of action is not fully understood. Herein, we report the identification of selenoprotein W (SELENOW) through large-scale mRNA profiling of receptor activator of nuclear factor (NF)-κΒ ligand (RANKL)-induced osteoclast differentiation, as a protein that is downregulated via RANKL/RANK/tumour necrosis factor receptor-associated factor 6/p38 signaling. RNA-sequencing analysis reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(66 citation statements)
references
References 72 publications
1
65
0
Order By: Relevance
“…Then, the femurs were embedded in paraffin, cross-sectioned at 8 μm in thickness, and stained using a TRAP staining kit. The number of osteoclasts per bone surface (N.Oc/BS) was calculated ( 35 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, the femurs were embedded in paraffin, cross-sectioned at 8 μm in thickness, and stained using a TRAP staining kit. The number of osteoclasts per bone surface (N.Oc/BS) was calculated ( 35 ).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, leucine-rich repeat-containing G protein-coupled receptor 4 (LGR4), which can compete with RANK in binding with RANKL, and TNF- antagonist etanercept, which can inhibit TNF- function, are considered beneficial for the treatment of osteoporosis (9,32). However, these RANKL/TNF- inhibitors, mostly protein drugs, often suffer from shortcomings such as short blood circulation time, suboptimal biodistribution, complex manufacturing processes, and resistance of antibodies (33)(34)(35). In addition, the pathological background of osteoporosis is often related to multiple targets, and thus, a single-target therapeutic modality may be suboptimal (36).…”
Section: Introductionmentioning
confidence: 99%
“…Selenoprotein W ensures physiological bone remodeling by preventing hyperactivity of osteoclasts. Study identifies selenoprotein W (SELENOW) as a protein down-regulated through RANKL/RANK/tumor necrosis factor receptor-associated factor 6/p38 signaling by large-scale mRNA analysis of nuclear factor (NF)-κΒ ligand (RANKL)-induced osteoblast differentiation ( Kim et al, 2021 ). RNA-sequencing analysis revealed that SELENOW regulates osteoclastogenic genes.…”
Section: The Differentiation Of Osteoclastsmentioning
confidence: 99%
“…RNA-sequencing analysis revealed that SELENOW regulates osteoclastogenic genes. SELENOW overexpression enhances osteoclastogenesis in vitro via nuclear translocation of NF-κB and nuclear factor of activated T-cells cytoplasmic 1 mediated by 14-3-3γ, whereas its deficiency suppresses osteoclast formation ( Kim et al, 2021 ). Major vault protein (MVP) (also known as lung resistance-related protein, LRP), is the main component of cellular ribonucleoprotein particles called vaults.…”
Section: The Differentiation Of Osteoclastsmentioning
confidence: 99%
“…A crucial component of the intracellular Recently, Kim et al demonstrated that SELENOW contributes to osteoclastogenesis, but is downregulated via RANKL/RANK/tumor-necrosis-factor-receptor-associated factor 6/p38 signaling. They suggested that this RANK-dependent inhibition of SELENOW blocks overactive osteoclasts to prevent osteoporosis [178]. SELENOP is a major selenium transporter in plasma that is produced and released by hepatocytes and resorbed by bone cells via apolipoprotein receptor 2(ApoER2) [179][180][181].…”
Section: Selenoproteins In Bone Metabolismmentioning
confidence: 99%